A chromatin modulator sustains self-renewal and enables differentiation of postnatal neural stem and progenitor cells. (23rd August 2019) - Shah, Kushani; King, Gwendalyn D; Jiang, Hao
Abstract: It remains unknown whether H3K4 methylation, an epigenetic modification associated with gene activation, regulates fate determination of the postnatal neural stem and progenitor cells (NSPCs). By inactivating the Dpy30 subunit of the major H3K4 methyltransferase complexes in specific regions of mouse brain, we demonstrate a crucial role of efficient H3K4 methylation in maintaining both the self-renewal and differentiation capacity of postnatal NSPCs. Dpy30 deficiency disrupts development of hippocampus and especially the dentate gyrus and subventricular zone, the major regions for postnatal NSC activities. Dpy30 is indispensable for sustaining the self-renewal and proliferation of NSPCs in a cell-intrinsic manner and also enables the differentiation of mouse and human neural progenitor cells to neuronal and glial lineages. Dpy30 directly regulates H3K4 methylation and the induction of several genes critical in neurogenesis. These findings link a prominent epigenetic mechanism of gene expression to the fundamental properties of NSPCs and may have implications in neurodevelopmental disorders.